Corelation Between Learning Motivation and Learning Outcomes of Senior High School Students in Heredity Material - Rahayu Rahayu; Mieke Miarsyah; Reni Indrayanti (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Learning outcomes is an ability that must be owned by learner after getting a learning experience. This ability is not an independent thing, but has correlation with many factors, such as learning motivation. The aim of this research is to know the correlationn between learning motivation and learning outcomes of senior high school students in Heredity materials. This research was conducted on students grade XII of SMA IT Thariq Bin Ziyad on first and second semester in the school year 2016/2017. Research method that is used is survey through correlational study. Data were collected by using questionnary for learning motivation, and test instrument for learning outcomes in Heredity material. All data were distribute normally and homogenuous. Data were analysed by simple linear regression test showed that regression equation y = 9,72 + 0,34x. Result of this research showed that there is possitive correlation between learning motivation and learning outcomes of students in Heredity materials with correlation coofisient 0,414. This result illustrate that higher learning motivation will make students’ learning outcomes in Heredity material become better. The other way, if students learning motivation is low, the learning outcomes will be low as well.Keywords: Learning motivation, learning ourcomes, Heredity material